Performance analysis of solar electric scooters with different charger controllers - Asrori Asrori; Sugeng Hadi Susilo; Satworo Adiwidodo; Elka Faizal; Mira Esculenta Martawati; Moh. Hartono (International Journal of Advances in Applied Sciences, 2024)
This study investigates the impact of solar charge controller (SCC) type on battery charging in solar-powered electric scooters (e-scooters). The research compared maximum power point tracking (MPPT) and pulse width modulation (PWM) controllers by monitoring average output power, current, and voltage every 10 minutes. Results showed that under stationary conditions, MPPT controllers delivered higher efficiency, generating 5.87 W of power compared to PWM's 5.05 W. This advantage persisted even during scooter operation, with MPPT controllers producing 4.91 W versus PWM's 4.31 W. Overall, the findings demonstrate that MPPT SCCs offer a more efficient solution for charging e-scooter batteries.